Replacing fish oil with crude palm oil in the diet of larval hybrid lemon fin barb Barbonymus gonionotusaA Hypsibarbus wetmoreia‚ - Weerasingha, Rochana; Kamarudin, Mohd Salleh; Karim, Murni Marlina Abd; Ismail, Mohammad Fadhil Syukri (Elsevier B.V., 2022)
Hybrid lemon fin barb is a novel carp species produced in Malaysia crossing lemon fin barb (Hypsibarbus wetmorei, ♂) and silver barb (Barbonymus gonionotus, ♀). As the delicious wild H. wetmorei is being overexploited, this new hybrid species is produced, filling the production gap in Malaysian aquaculture. The hybrid larvae in our previous study showed high tolerance to bacterial diseases and revealed the suitability of culturing hybrid lemon fin barb in the tropics. The effects of increasing dietary replacements level of fish oil (FO) with crude palm oil (CPO) were investigated for the larval stage of this fast-growing and delicious carp species. Three-day old hybrid larvae were randomly allocated to fifteen 5-L tanks stocked at the rate of 50 larvae L−1. Five micro diets containing 0%, 25%, 50%, 75% and 100% dietary substitution levels of FO with CPO levels were formulated. An extra replicate tank was maintained for each treatment for enzyme sampling at 4-day intervals. After 20 days of the feeding trial, dietary replacement of FO with CPO did not significantly affect (p > 0.05) survival and growth of hybrid lemon fin barb larvae. Dietary CPO reduced (p < 0.05) docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) in hybrid larval tissues. Partial replacement of FO with CPO in hybrid lemon fin barb diets showed no lipid vacuoles in the liver and gut during the challenge test against A. hydrophila. In conclusion, total replacement of FO with CPO is acceptable for the culture of hybrid lemon fin barb larvae; though considering the health status of larvae, 75% replacement of dietary FO with CPO would be more applicable. However, lipid metabolism seems low at the early larval period in larvae fed dietary CPO.